Improved Scoring of Lund Mackay Score (LMS) - Satyendra Nath Chakrabartty (ENT Updates, 2024)
Lund Mackay Score (LMS), modified Lund Kennedy (MLK) scores quantify degree of opacification for each sinus by numerical scoring systems. Correlations between LMS on paranasal sinus CT scans, MLK nasoendoscopic scores and associated tools like SNOT-22, RSDI, EPOS, PROMIS-29, etc. showed contrasting empirical results. The paper discusses methodological limitations of numerical scoring systems and provides a method of transforming ordinal discrete scores of a multi-point item to normally distributed proposed scores). Scale scores -scores) as sum of s also follow normal distribution and can include all indicators irrespective of scale formats. Normality of monotonically increasing P-scores and -scores of LMS/MLK satisfy desired properties, provide unique ranks to the individuals, facilitate parametric analysis for diagnosis (ROC analysis), classification and comparisons of different aspects of chronic rhinosinusitis measured by LMS/MLK and subjective measures of symptom scores reflecting disease severity. The method also facilitates statistical tests of equality of mean and variance of LMS/MLK for two groups or a single group at different time periods, significance of disease progression and better computation of reliability, factorial validity. Proposed method can better assess severity/disability of CRS and include all tools (pathological, clinical, patient-reported- outcomes and HRQoL instruments) irrespective of scale formats without any bias for advantaged or disadvantaged groups